Outcomes of Balloon Occluded Retrograde Transvenous Obliteration Performed in Patients with Solitary Gastric Varices - Kondou, Eisaku; Matsuzaki, Hiroshi (Japanese Journal of Portal Hypertension, 1999)
Since 1992 we have used balloon occluded retrograde transvenous obliteration (B-RTO) for the primary treatment of solitary gastric varices. The selection criteria of patients include sufficiently prolonged filling of the contrast medium on varicography. Subjects were 22 patients admitted to our hospital for the treatment of gastric varices between March 1992 and February 1998. Therapeutic efficacy, recurrent rate, influence on coexisting esophagealvarices and adverse effects were evaluated during the observation period from 1 month to 6 years (average 2.2 years) after treatment. Gastric varices completely disappeared and no recurrence was observed in 21 of the 22 patients treated. Of these, collateral circulation seen as gastrorenal shunt disappeared in 16, but persisted in 2. The result was unclear in 3 patients. Treatment of coexisting esophageal varices was needed in 9, and the cumulative reappearance rates were 25.3% and 50.2% at 3 years and 5 years after treatment, respectively. Concerning adverse effects, fever higher than 38°C, pleural effusion chest pain and abdominal pain were observed in 70%, 50%, 35% and 30% of the patients, respectively. The levels of AST, ALT, BUN and creatinine showed negligible changes after the treatment. Levels of total bilirubin and LDH showed significant but temporary elevation after the treatment. These results indicate that B-RTO is a safe and reliable method for solitary gastric varices.